KEMAMPUAN MENGANALISIS PERMASALAHAN LINGKUNGAN SUNGAI CITARUM: LITERASI EKOLOGI DAN MODEL PEMBELAJARAN ILMIZI - Rita Istiana; Rita Retnowati; Suci Putri Lestari; Ilmi Zajuli Ichsan; Yohamintin Yohamintin; Yeni Widiyawati; Trio Ageng Prayitno (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2020)
This study aimed to obtain information about the relationship between students' abilities in analyzing environmental problems in the Citarum Watershed (DAS) and ecological literacy. In addition, to find out other factors that have a relationship with the ability of students to analyze environmental problems in the Citarum watershed and to analyze the ILMIZI model as an innovative learning model. This research was conducted from January to July 2020. Retrieval of quantitative data using test questions in the form of descriptions for variable Y and a combination of questionnaires and items for variable X. After the Pearson product moment correlation test was carried out, it was found that there was a low category positive relationship between ecological literacy and students' ability to analyze environmental problems in the Citarum watershed because it was still the low interest in reading students. Results of regression equation Ŷ = 88.025 + 0.474x with a correlation coefficient of r = 0.22 and r2 of 5.04%. The results of the ILMIZI learning model analysis showed that this model relevant to improve students' analytical skills. The conclusion of this study is that there is a low positive relationship between ecological literacy and students' ability to analyze environmental problems, and it can be improved with the ILMIZI model.